Proceeding The 2nd International Seminar of Language, Education and Culture of Faculty of Language, Education, and Culture, Universal University and The 3rd International Seminar of Association of Indonesia Mandarin Studies Program (5-6 Agustus 2022) - Indonesia dan Universitas Universal, Asosiasi Program Studi Mandarin (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2022)
-